1993
DOI: 10.1017/s0260305500012751
|View full text |Cite
|
Sign up to set email alerts
|

Satellite passive microwave observations and analysis of Arctic and Antarctic sea ice, 1978–1987

Abstract: We have recently completed an analysis that examines in detail the spatial and temporal variations in global sea-ice coverage from 26 October 1978, through 20 August 1987. The sea-icemeasurements we analyzed are derived from data collected by a multispectral, dual-polarized, constant incidence-angle microwave imager, the Scanning Multichannel Microwave Radiometer (SMMR) on board the NASA Nimbus 7 satellite. The characteristics of the SMMR have permitted a more accurate calculation of total sea-ice concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 3 publications
3
62
0
1
Order By: Relevance
“…Multiyear ice has been defined by WMO as ice that has survived at least two summer periods and is the thick component of the perennial ice cover which includes the relatively thinner second year ice cover. The difference in the signature of multiyear ice compared with seasonal ice has been reported previously (Vant et al, 1978) and has been confirmed using satellite data (e.g., Gloersen et al 1992;Comiso, 2006). The study of the multiyear ice cover as described is important because it enables the assessment of changes and trends in the extent and area of this thick ice type over the more than three decades of continuous satellite observations.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Multiyear ice has been defined by WMO as ice that has survived at least two summer periods and is the thick component of the perennial ice cover which includes the relatively thinner second year ice cover. The difference in the signature of multiyear ice compared with seasonal ice has been reported previously (Vant et al, 1978) and has been confirmed using satellite data (e.g., Gloersen et al 1992;Comiso, 2006). The study of the multiyear ice cover as described is important because it enables the assessment of changes and trends in the extent and area of this thick ice type over the more than three decades of continuous satellite observations.…”
Section: Introductionsupporting
confidence: 58%
“…We assume that the data in the AD cluster represents mixtures of seasonal and multiyear ice cover with those near the label A representing 100% first year ice while those near the label D representing near 100% multiyear ice. Using the aforementioned mixing algorithm, the concentration of multiyear ice is estimated but instead of the reference points being fixed for all months and all years, as in Gloersen et al (1992) and Johannessen et al (1999), we used a dynamic reference point for 100% multiyear ice as indicated earlier. Such adjustment is made based on the frequency distribution of the AD cluster and is done consistently for the entire satellite data set.…”
Section: Multiyear Ice Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…By using in-situ observations of sea ice thickness, snow depth and freeboard from 15 research cruises into the Southern Ocean [6] proposed a suite of regional empirical linear relationships that allow computing snow depth on sea ice from total freeboard measurements. The empirical relationships are derived for five different regions in the Southern Ocean: Western Weddell Sea (WSW), Eastern Weddell Sea, Eastern Antarctic (EA), Ross Sea, and Bellingshausen-Amundsen Sea [6]; see [39] and [23] for a more detailed definition of these regions. Single measurements carried out along survey lines with an average length of~50 m across ice floes were averaged to obtain survey line mean values of total freeboard and snow depth.…”
Section: Methodsmentioning
confidence: 99%
“…For the period 1979-2010, the annual mean extent of sea ice showed a decrease of more than 4% per decade [8]. While a decreasing trend for the total extent of Arctic sea ice is apparent for all months [8,9], the trend is greatest in summer [1,10], when the sea ice extent is at its lowest annual value [11][12][13][14]. The month showing the minimum sea ice is September, with a downward trend of more than 12% per decade for the period 1979-2010 [1,10].…”
Section: Introductionmentioning
confidence: 97%